Correlation Between PSA Density and Gleason Score In Prostate Cancer Patients - Yusuf, Md Naved; Gupta, Sudip Das; Rahman, Mohammed Mianur; Rahman, Md Mahmud Ur (Bangladesh Journal of Urology, 2020)
Background: Prostate cancer is the most common form of malignancy and the second leading cause of cancer death among men. The histological grade is an independent determinant of disease prognosis and survival. The Gleason System (GS) grading is the most widely accepted classification. Several recent studies have searched for factors that could predict GS upgrading. High prostate specific antigen density (PSAD) has been shown to be predictors of risk progression in many studies, reflecting the possibility of undetected aggressive cancer. Objective: To detect the association between PSA density and Gleason score in prostate cancer patients. Methodology: This cross sectional study was carried out at the department of urology, Sir Salimullah Medical College Mitford hospital, Dhaka. Patients diagnosed as prostate cancer meeting the inclusion criteria admitted in the above mentioned place was the study population. Statistical analyses were carried out by using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Student t-test was used for continuous variables. Pearson’s correlation coefficient was used to test the relationship between the groups. P values <0.05 was considered as statistically significant. Results: Total eighty three patients were included in this study. The mean age was found 69.2±7.7 years ranging from 50 to 85 years. The mean volume of prostate was 42.3±17.6 ml ranging from 13.0 to 68.0 ml. The mean Gleason score was 7.8±1.4 ranging from 6.0 to 10.0. More than one third (33.7%) patients had PSA density 0.15- 0.5 ng/ml/ml. Three patients had found Gleason score 9 (5+4) within PSA density 0.51-1.0 ng/ml/ml, 5 patients within PSA density 1.1-1.5 ng/ml/ml, 3 patients within PSA density 1.51-2.0 ng/ml/ml, 6 patients within PSA density 2.1-2.5 ng/ml/ml, 5 patients within PSA density 2.51-3.0 ng/ml/ml and 2 patients within PSA density >3.0 ng/ml/ml. The difference was statistically significant (p<0.05) among seven groups. Positive correlation (r=0.717; p=0.001) between PSA density with Gleason score. Conclusion: In this study, we find there is a strong correlation between PSA density and Gleason score. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.164-168